Pengaruh Aromaterapi Lemon Terhadap Pengurangan Mual Muntah Pada Ibu Hamil Trimester I Di Klinik Hj.Dermawati - Muthia Sari Mardha; Endryani Syafitri; Ivansri Marsaulina; Aulia Rizky Fadila (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
During the first trimester of pregnancy, nausea and vomiting are frequently experienced. Vomiting and nausea are most common in the morning, yet can happen at any time of day or night. It will cause difficulties for the fetus and pregnant women if left untreates. Both pharmaceutical and non pharmacological therapies, such as lemon aromatherapy, can be used to treat emesis gravidarum. This study aimed to determine the effect of lemon aromatherapy on reducing nausea and vomiting in first trimester pregnant women.This was quasi experiment with one group pretest-posttest research. The population in this study were 25 first trimester pregnant women at the clinic with a gestational age of 1-2 weeks. The sample of this study amounted to 25 first trimester pregnant women with gestational age 1-12 weeks. Data analysis used univariate and bivariate analysis and tested by T-tes.According to the study’s findings, which were based on the frequency of nausea and vomiting before receiving aromatherapy, the majority of respondents-16 people, or 64% of the sample-experienced moderate nausea and vomiting, followed by mild nausea and vomiting (6 people, or 24%) and severe nausea and vomiting (3 people, or 12%). After receiving aromatherapy, the number of respondents decreased to 14 people, or 56% and 11 people, or 44% experienced no nausea and vomiting. It is known that p = 0,003 based on statistical test findings, specifically the independent t test with a 95% confidence level.The result showed that, lemon aromatherapyh had an impact in lowering nausea and vomiting in first-trimester pregnant women. It is suggested that pregnant women explore the benefits of lemon aromatherapy for reducing nausea and vomiting by reading print and digital sources.